Sistem Pendukung Keputusan Pemilihan Guru TIK Berprestasi Menggunakan Metode SMART - Yuri Rahmanto (PT. Tech Cart Press, 2024)
Information and Communication Technology (ICT) teachers are educators who have a vital role in teaching technology-related skills and knowledge to students, with the aim of equipping them to face the digital era. One of the main problems is the use of traditional methods that are subjective or the lack of a data-driven decision support system, which can lead to biased selection results. As a result, the potential of teachers who are actually superior may not be well identified, which can have an impact on the overall quality of ICT learning. ICT teachers are often associated with the standardization of assessment criteria that are inconsistent or less objective, and the selection process often relies on personal assessments or opinions that can vary from one evaluator to another, resulting in decisions that are not always objective. The application of the SMART method in SPK to determine outstanding ICT teachers. This study uses a number of assessment criteria, such as pedagogical competence, mastery of ICT materials, innovation ability in learning, communication skills, and contribution to student achievement. The results show that the SMART method can accommodate the assessment systematically and objectively, providing the best teacher recommendations with high transparency. The ranking results show the performance of outstanding ICT teachers based on the total score obtained. Teacher E ranked first with the highest score of 0.9049, which reflects a very superior performance compared to other teachers. In second place, Teacher B got a score of 0.8096, showing a very good performance, although slightly below Teacher E. Teacher A was ranked third with a score of 0.5953, showing a fairly good performance but still far from the top two rankings.